Characteristics and mechanical properties changes due to incorporation of aloe vera in polyethylene-based film / Siti Fatma Abd Karim …[et al.] - Abd Karim, Siti Fatma; Jai, Junaidah; Ku Hamid, Ku Halim; Abdul Jalil, Abdul Wafi (Universiti Teknologi MARA Shah Alam, 2020)
Non-degradable properties of polyethylene (PE) films due to long-chain structure cause increment of solid waste plastic. Many researchers, with different purposes, have studied the incorporation of functional materials to PE. Exploring the impact of the incorporation of aloe Vera (AV) into PE films in terms of its characteristic and mechanical properties is the main objective of this paper. The films were prepared using melt-blending and hot press technique. The characterisation assessed for the PE and PE-AV films were spectroscopy, crystalline phase, thermal analysis, and performance of the mechanical properties of the sample. Some of the AV functional groups disappeared upon addition with PE but has the possibility of two sharing peaks between AV and PE, which was 1472 and 2915 cm-1. Lower thermal degradation temperature (Td) obtained for PE-AV3 while other films found no significant changes in Td value, and only one peak of thermal degradation occurred for all films. The same goes for the analysis obtained from differential scanning calorimetry (DSC) data. However, the crystalline structure displayed momentous peak changes for PE with AV. The highest tensile strength (TS) obtained by PE-AV3, at once, developing the highest value of Young’s modulus (YM), modulus of resilience (UE), and modulus of toughness (UT). A certain amount of AV has a substantial effect on changing the polymeric structure, especially improving the mechanical properties of PE film. Therefore, AV has the potential to become an additive for developing a new, partially degradable PE film.